(untitled) (Raparin Journal of Humanities (RJH), 2026)
One of the philosophers of the Enlightenment is “Jean-Jacques Rousseau”, although he was not a successful father, because he left his children in an orphanage after he separated from his wife. However, he was able to establish an educational and training method for the world - which most countries follow today -and put it under the name "Emile" and the style of this book was similar to the style of writing a novel, that is, making "Emile “a character for a child and through this child he established the principles of education. After this book was published, he returned to the orphanage to get his children back, but it was too late because they were given to families who did not own the children, and thus "Rousseau" lost his children because they changed the names and did not know which family had taken his child or children. Middle Eastern societies in general have their own rules and principles, as most countries apply the rules of the clan or the prevailing social system is left by feudal lords and money owners; therefore, people’s livelihood is at the mercy of these people. The novel "Al-Ansar" is one of the Kurdish novels in which the writer was able to embody the character of "Emil" the child with the character of a child in the adolescent stage, “Saeed" .In this way, the writer shed light on the prevailing customs and traditions of Kurdish society in a specific area, as well as the strict paternal authority and the injustice that followed it and emotional deprivation, all of this on one hand and taking children out of schools to work in the markets while they are in a stage where they need to be satisfied by playing and enjoying childhood on the other hand. Through this novel, it became clear that Kurdish society at that time was going against the direction of Rousseau’s educational principles. Therefore, we find that children who live in a restrictive environment will have weak personalities. Therefore, he chose this novel as an opportunity to show the prevailing educational system in some societies.